Selective cytotoxicity mechanisms and biodistribution of diamond nanoparticles on the skin cancer in C57 mouse. (16th December 2021) - Moradi, Elham; Naserzadeh, Parvaneh; Brouki Millan, Peiman; Ashtari, Behnaz
Abstract: The cytotoxicity of diamond nanoparticles (DNs) to various cell lines has been on focus by numerous scientists. The cellular toxicity system of DNs has not been fully understood or explained in skin cancer, at this point. This research was carried out to discover and reveal the potential impacts of DNs on the secluded brain, heart, liver, kidney, and skin in addition to evaluation of their cytotoxicity mechanism under test conditions. Their biological activities, for example cell viability, the level of reactive oxygen species (ROS), lipid peroxidation, cytochrome c release and Apoptosis/Necrosis were evaluated. Additionally, the bio-distribution of these nanomaterials in tissues was examined in the C57 mouse. Relying on the findings of the investigation, DNs were found to increase the ROS level, Malondialdehyde (MDA) content, release of cytochrome c, and cell death in skin significantly compared to other groups. In the C57 mouse, DNs were observed to have accumulated in skin tissue more intensively than they did in other organs. The present study presents for the proof that DNs can completely induce cell death signaling in skin cancer without bringing about a high cytotoxicity in other tissues. Results suggest that DNs can be valuable in recognition of skin cancer.